Hubungan Durasi Duduk dan Frekuensi Olahraga dengan Derajat Fungsional Low Back Pain pada Pegawai di Sekretariat Daerah Kota Cirebon - Lintang Azahra Anggun Pratiwi; Kati Sriwiyati; Moh Irwan Dharmansyah (KOLONI, 2026)
Low Back Pain (LBP) is a musculoskeletal disorder commonly experienced by office workers due to prolonged sitting duration and low physical activity. This condition may reduce functional ability and work productivity. This study aimed to analyze the relationship between sitting duration and exercise frequency with the functional degree of Low Back Pain among employees at the Regional Secretariat of Cirebon City. This study used an observational analytic design with a cross-sectional approach. The population consisted of civil servant employees at the Regional Secretariat of Cirebon City with a total sample of 38 respondents selected using consecutive sampling technique. Independent variables were sitting duration and exercise frequency, while the dependent variable was the functional degree of Low Back Pain. Data were collected using sitting duration questionnaires, exercise frequency questionnaires, and the Back Pain Functional Scale (BPFS). Data analysis was performed using univariate and bivariate analysis with Spearman correlation test at a significance level of p<0.05. Most respondents had prolonged sitting duration (>4 hours/day) as many as 24 respondents (63.2%) and occasional exercise frequency (1–2 times/week) as many as 26 respondents (68.4%). The median functional degree of Low Back Pain was 92.5% ± 8.92%. Statistical analysis showed no significant relationship between sitting duration and the functional degree of Low Back Pain (p=0.345), as well as between exercise frequency and the functional degree of Low Back Pain (p=0.413).There was no significant relationship between sitting duration and exercise frequency with the functional degree of Low Back Pain among employees at the Regional Secretariat of Cirebon City.